2014
DOI: 10.1021/ac503577t
|View full text |Cite
|
Sign up to set email alerts
|

Detection of UV-Induced Mutagenic Thymine Dimer Using Graphene Oxide

Abstract: In this paper, we report for the first time that graphene oxide (GO) can interact with mutagenic DNA but not intact DNA. After UV-irradiated fluorophore-linked DNA containing thymine repeats was mixed with GO, a decrease in fluorescence was observed in a time-dependent manner. In contrast, no fluorescence change was observed with intact DNA, indicating that UV irradiation of DNA resulted in the formation of mutagenic bases. Because GO is known to act as a fluorescence quencher, the decreased fluorescence impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, it was reported that purine dimers formed between two adenines and between adjacent purines and pyrimidines [ 24 ]. Previously, it was reported that formation of dimers within DNA increased affinity of GO to the mutated DNA [ 19 ]. No significant changes in DOF of the GO-DNA mixtures in the absence of KP even after 40 min of irradiation with UV light confirmed no noticeable formation of purine dimers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was reported that purine dimers formed between two adenines and between adjacent purines and pyrimidines [ 24 ]. Previously, it was reported that formation of dimers within DNA increased affinity of GO to the mutated DNA [ 19 ]. No significant changes in DOF of the GO-DNA mixtures in the absence of KP even after 40 min of irradiation with UV light confirmed no noticeable formation of purine dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the selective affinity to ssDNA, and highly effective fluorescence quenching ability, GO has been applied to detect various targets such as heavy metals, small molecules and nucleic acids [ 18 ]. Previously, a GO based method to detect DNA photodimers and screen dimer-photosensitizing drugs was reported [ 19 ]. However, it is not yet reported if GO could be applied to detect the SDBs and screen photosensitizing drugs.…”
Section: Introductionmentioning
confidence: 99%
“…19 Traditional fluorescent methods make it difficult to get good sensitivity and a high signal-to-background ratio. [20][21][22] Thus, the development of a simple, convenient and sensitive method to detect the damage of DNA by UV radiation is highly desirable.…”
Section: Introductionmentioning
confidence: 99%